Evaluating The Impact of Classroom Cleanliness Competitions on Primary Students’ Environmental Awareness - Muhamad Tolhani,; Aliet Noorhayati Sutisno,; Fanny Septiany Rahayu, (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of classroom cleanliness competitions on students' environmental awareness at SDN 1 Karanganyar. This study uses a quantitative approach with a survey method. The population consists of 332 students, with a sample of 33 students selected using cluster random sampling. The research instruments are environmental awareness questionnaires and observation sheets, which have undergone validity and reliability tests. Data analysis was conducted using simple linear regression. The results indicate that classroom cleanliness competitions do not significantly influence students' environmental awareness, with a t-test significance value of 0.348 > 0.05 and an F-test value of 0.348 > 0.05. The coefficient of determination (R²) value of 0.291 indicates that the classroom cleanliness competition contributes 29.1% to the variation in students' environmental awareness levels, while the remaining 70.9% is influenced by factors outside the scope of this study. The conclusion of this study indicates that although classroom cleanliness competitions can serve as a medium for character education, their implementation has not yet been able to significantly influence the improvement of students' environmental awareness.